Part I: synthesis of azaheterocycles from aryl ketone O-acetyl oximes and internal alkynes by Cu-Rh bimetallic relay catalysts. Part II: Synthesis of 3,4-2H-dihydropyrroles starting from alkenyl carbonitriles and grignard reagents via Cu(II)-mediated iminooxygenation of N-H imines with tempo - Chua, Sze Hui (2013)
Nitrogen-containing heterocycles, also known as azaheterocycles, are important subunits of numerous natural products and are responsible for exhibiting a wide range of biological activities.